STUDI PERBANDINGAN METODE MUBĀSYARAH DENGAN METODE HERBARTH PADA HASIL PEMBELAJARAN NAḤWU - Safaruddin Safaruddin; Hamka Ilyas; Munir Alimuddin (STIQ Amuntai, 2022)
Based on the observations of the researchers, in learning Arabic, especially in the Naḥwu subject, the use of the lecture method, the rule and translation method, and the reading method were, in fact, less effective looking at the mid-semester exam results, the average student got a low score below the average. On average, on that basis, the researcher will offer a Mubāsyarah Method and the Herbarth Method to have experimented with the intent and purpose of improving student learning outcomes in the Naḥwu class II KMI learning outcomes at the Darul Huffadh Tuju-Tuju Islamic Boarding School, Kajuara Bone. The type of research in this scientific paper is quantitative research with an experimental research model. In this study, the researcher is a teacher directly supervised by one of the nahwu Pondok subject teachers. So in this research, the researcher applies the mubāsyarah method first and then the herbārth method in naḥwu learning. The method of collecting data is by testing, observing, and documenting using XL Microsoft in finding the average value. Based on the results of the recap of the average values of the classes (II B & II C), it was concluded that the herbārth method was more effective after being compared to the results of the mubāsyarah method with the average results of the mubāsyarah method in class II B 7.2 and II C 6 and the herbārth method II B 8.6 and II C 7.7.Keywords: Mubāsyarah Method, Herbārth Method, Nahwu Learning.